Molecular Detection of Bartonella sp. in Psathyromyia shannoni and Lutzomyia cruciata From Northeastern Mexico - Lozano-Sardaneta, Yokomi N.; Soto-Olguín, Nadia Joselyne; Rodríguez-Rojas, Jorge J.; Sánchez-Montes, Sokani; Rebollar-Téllez, Eduardo A.; Becker, Ingeborg (Frontiers in Tropical Diseases, 2021)
Phleotomine sand flies are vectors of Leishmania spp., Bartonella bacilliformis and several arboviruses worldwide. In Mexico, the presence of Bartonella species is associated sporadically with arthropods and little is known on the diversity of insects that could be incriminated with its transmission. The aim of this study was to perform a molecular detection of Bartonella DNA in sand fly species collected in the northeastern Mexico. Sand flies were collected at the states of Nuevo Leon and Tamaulipas from June to August 2010, using 16 light traps per night. Sand fly species were morphologically identified and for Bartonella detection, we amplified ~378 bp of the citrate synthase gene (gltA). DNA sequences were compared in a phylogenetic reconstruction based on the Maximum Likelihood. A total of 532 specimens from seven sand fly species were morphologically identified, where 11 specimens from Tamaulipas tested positive for the presence of a new lineage of Bartonella sp. associated with Psathyromyia shannoni and Lutzomyia cruciata. This work represents the second record of Bartonella-associated with sand flies outside of the endemic area of Carrion´s disease. More studies are necessary to understand their life cycle, transmission dynamics, and their relationship with sand fly species.